Historical dictionary of the Orthodox Church - Prokurat, Michael (Historical dictionaries of religions, philosophies, and movements, 1996)
Of the three major branches of Christianity, Orthodoxy is the least known and most misunderstood. The Historical Dictionary of the Orthodox Church provides students, researchers, and specialists with a desk encyclopedia of the theology and theologians, saints, sinners, places and events of the Eastern Church. Two millennia of the religion are surveyed in over five hundred concise entries, concentrating primarily on the last 150 years. Includes an overview of the early Church through the Byzantine and Russian Empires, into the present multinational Orthodox presence in the ecumenical movement. Many of the general entries cannot be found elsewhere in English, and the comprehensive compilation of biographies of nineteenth- and twentieth-century Orthodox theologians (American, Russian, Greek, and many other nationalities) is published here for the first time. Includes a detailed 4000-year chronology, illustrations, extensive bibliography, and an appendix listing the current canonical patriarchs and autocephalous churches.